Bovine explant model of degeneration of the intervertebral disc - Roberts, Sally (BioMed Central, 2008)
BACKGROUND: Many new treatments for degeneration of the intervertebral disc are being developed which can be delivered through a needle. These require testing in model systems before being used in human patients. Unfortunately, because of differences in anatomy, there are no ideal animal models of disc degeneration. Bovine explant model systems have many advantages but it is not possible to inject any significant volume into an intact disc. Therefore we have attempted to mimic disc degeneration in an explant bovine model via enzymatic digestion. METHODS: Bovine coccygeal discs were incubated with different concentrations of the proteolytic enzymes, trypsin and papain, and maintained in culture for up to 3 weeks. A radio-opaque solution was injected to visualise cavities generated. Degenerative features were monitored histologically and biochemically (water and glycosaminoglycan content, via dimethylmethylene blue). RESULTS AND CONCLUSION: The central region of both papain and trypsin treated discs was macro- and microscopically fragmented, with severe loss of metachromasia. The integrity of the surrounding tissue was mostly in tact with cells in the outer annulus appearing viable. Biochemical analysis demonstrated greatly reduced glycosaminoglycan content in these compared to untreated discs. We have shown that bovine coccygeal discs, treated with proteolytic enzymes can provide a useful in vitro model system for developing and testing potential new treatments of disc degeneration, such as injectable implants or biological therapies.